Plantar hemangioma. - Milano, A. (European Journal of Pediatric Dermatology, 2010)
The diagnosis of hemangioma (2) is based on the epidemiological criterion -it is the more frequent tumor of the first months (1)-, on the clinical history -a proliferation growing in the first months, reaches the maximum size around the fourth month and then remains stable before regressing slowly in years-, on the blood red color of its superficial component or sometimes bluish of its deep component, on its soft compressible consistency, on the increased temperature due to its increased amount of blood and on the increased visibility under the conditions causing vessel dilatation. On ultrasonography, hemangioma is characterized by (3) high density of vessels, high Doppler shift, low resistance, and scarcity or lack of arteriovenous shunts in its inside. Magnetic resonance showing the nourishing and draining vessels is more useful but of more difficult execution. It is unlikely that no one of these criteria is present. However, this can occur in deep hemangiomas during the phase of rapid growing, all the more so when the thickness of the skin is increased as in the plantar region. In our two cases the clinical history was not diriment, a slight erythema was present only in case 2, but there was no significant discoloration in case 1, the consistency was tense due to the lack of blood lacunae, the increase of local temperature was not significant and the neoformations did not get more visible when preventing the venous return with the pressure of the fingers. The ultrasonography changes were not appreciated due to the scarce knowledge of skin vascular disorders by the ultrasound operators. Due to all these reasons we performed in both cases a skin biopsy. The latter is not usually performed in hemangioma because the clinical diagnosis is very evident. In both cases it was diriment, showing a proliferation of endothelial vessel forming cells.